2010
DOI: 10.1111/j.1423-0410.2010.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparummalaria and the immunogenetics of ABO, HLA, and CD36 (platelet glycoprotein IV)

Abstract: Plasmodium falciparum malaria has long been a killer of the young, and has selected for polymorphisms affecting not only erythrocytes, but the immunogenetics of three histocompatibility systems: ABO, human leukocyte antigen (HLA), and CD36. The ABO system is important because the original allele, encoding glycosylation with the A sugar, acts as an adhesion ligand with infected red blood cells (iRBC), thereby promoting vasoocclusion. The prevalence of blood group O, which reduces this cytoadhesion, has increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 117 publications
(146 reference statements)
2
20
0
Order By: Relevance
“…Persistence of protection after leaving malaria-endemic areas has already been suggested, but few biological data on immune responses are available [29, 30]. However, the differences in clinical presentation, observed in second-generation migrants and travelers/expatriates suggest the possibility that other factors are involved in protection against SM [31, 32]. Moreover, the difference in antibody response between first-generation migrants and second-generation migrants may also result from differences in exposure to the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of protection after leaving malaria-endemic areas has already been suggested, but few biological data on immune responses are available [29, 30]. However, the differences in clinical presentation, observed in second-generation migrants and travelers/expatriates suggest the possibility that other factors are involved in protection against SM [31, 32]. Moreover, the difference in antibody response between first-generation migrants and second-generation migrants may also result from differences in exposure to the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their intracellular development, remarkable immune evasion is achieved. The erythrocyte is arguably appealing not only for its nutritive iron and protein content, but also for its lack of continued HLA expression after enucleation [51], thereby unable to process and present immunologic signature units for adaptive immune recognition [52].…”
Section: Malariamentioning
confidence: 99%
“…It has recently been suggested that this severe infection may have played an important role in driving the current ABO distribution among populations in endemic areas [15][16][17][18][19][20][21][22][23]. In a recent review, Cserti and Dzik critically analyzed the literature on the association between the ABO system and P. falciparum malaria, showing that group O subjects tend to exhibit a favorable outcome than group A individuals [18]. In their experimental studies, Fry and colleagues [22] and Rowe and colleagues [21] provided a biological explanation for this clinical finding.…”
Section: Abo and Infectious Diseasesmentioning
confidence: 99%